Spontaneously dislocated lens with ring-shaped pigmentation - Dave, Parth; Sonawane, Nikita J. (Digital Journal of Ophthalmology, 2026)
A 78-year-old man presented at Aravind Eye Hospital, Puducherry, with a 2-year history of poor vision in the left eye. He had no history of trauma or cataract surgery. On examination, best-corrected visual acuity in the left eye was 2/60. Slit-lamp examination showed a nondilating pupil measuring 2 mm diameter, with aphakia in the pupillary plane. B-scan ultrasound was suggestive of a spontaneously dislocated lens. During pars plana vitrectomy, spontaneously reattached retina was noted, with atrophy, and the lens with a near mature nucleus, outlined by a pigmentary ring, was located at the demarcation line.